The Role of Bariatric Surgery in the Resolution of Type 2 Diabetes Mellitus - Khan, Yasmin (Trinity Student Medical Journal, 2007)
Obesity is a major risk factor for many diseases, most notably for type 2 diabetes. Due to this correlation, weight loss has been a primary objective in managing type 2 diabetes. Current medical weight loss therapies and programs have proved disappointing, presenting an increasingly frustrating problem for the obese and diabetic population. At present, bariatric surgery is the most effective treatment for obesity and type 2 diabetes by inducing significant, long-term weight reduction. The cornerstone for inducing weight loss in these procedures comprises elements of gastric restriction, malabsorption by means of bypassing the foregut, or a combination of both. Depending on the type of bariatric procedure, observation of euglycaemia has been found in 48% to 99% of cases following surgery, therefore proving to be far more superior in treating obesity and type 2 diabetes in comparison to nonsurgical methods. While weight loss may seem like the most reasonable explanation in the improved glycaemic control, several findings have suggested the involvement of other factors. Interestingly, the alterations of various gastrointestinal hormones imparted by the malabsorptive procedures appear to be the dominant feature in the resolution of type 2 diabetes. This article provides an overview of the various bariatric procedures and the physiological mechanisms that contribute to the weight loss and cure of type 2 diabetes after surgery